Potential Maternal Effects of Elevated Atmospheric CO2 on Development and Disease Severity in a Mediterranean Legume - Grünzweig, José M. (Frontiers in Plant Science, 2011)
Global change can greatly affect plant populations both directly by influencing growing conditions and indirectly by maternal effects on development of offspring. More information is needed on transgenerational effects of global change on plants and on their interactions with pathogens. The current study assessed potential maternal effects of atmospheric CO2 enrichment on performance and disease susceptibility of first-generation offspring of the Mediterranean legume Onobrychis crista-galli. Mother plants were grown at three CO2 concentrations, and the study focused on their offspring that were raised under common ambient climate and CO2. In addition, progeny were exposed to natural infection by the fungal pathogen powdery mildew. In one out of three years, offspring of high-CO2 treatments (440 and 600 ppm) had lower shoot biomass and reproductive output than offspring of low-CO2 treatment (280 ppm). Disease severity in a heavy-infection year was higher in high-CO2 than in low-CO2 offspring. However, some of the findings on maternal effects changed when the population was divided into two functionally diverging plant types distinguishable by flower color (pink, Type P; white Type W). Disease severity in a heavy-infection year was higher in high-CO2 than in low-CO2 progeny in the more disease-resistant (Type P), but not in the more susceptible plant type (Type W). In a low-infection year, maternal CO2 treatments did not differ in disease severity. Mother plants of Type P exposed to low CO2 produced larger seeds than all other combinations of CO2 and plant type, which might contribute to higher offspring performance. This study showed that elevated CO2 potentially exerts environmental maternal effects on performance of progeny and, notably, also on their susceptibility to natural infection by a pathogen. Maternal effects of global change might differently affect functionally divergent plant types, which could impact population fitness and alter plant communities.